De Novo CD5+ Primary Gastrointestinal Diffuse Large B-Cell Lymphoma: Challenges With Treatment and Clinical Course - Preethi Ramachandran MD; Sonu Sahni MD; Jen C. Wang MD (SAGE Publishing, 2019)
The gastrointestinal tract is a common extranodal site for lymphomas. However, primary gastrointestinal lymphomas are rare. Diffuse large B-cell lymphomas (DLBCL) are the most commonly encountered type in the gastrointestinal tract. Most of the DLBCL are CD5 negative. CD5+ DLBCL is very rare and a poor prognostic subtype of lymphoma. We report a rare case of primary small bowel CD5+ DLBCL that evolved from being a localized low International Prognostic Index-scored disease into an advanced and aggressive disease primarily dictated by the presence of CD5 antigen positivity.